Inhibitory effect and molecular mechanism on polyphenol oxidase by ultraviolet-C and L-cysteine treatment - Le Cheng; Haoyue Bai; Mingfang Zhang; Fengping Yang; Difeng Ren; Yunpeng Du (Current Research in Food Science)
The emerging technology of inhibiting polyphenol oxidase (PPO) is crucial for preventing enzymatic browning in food. This study aimed to investigate the effects of 4.5 kJ/m2 ultraviolet (UV)-C radiation and 0.02 mg/mL L-cysteine (L-cys) treatment on the enzyme activity, physico-chemical properties, thermal properties, structure, and molecular microstructure of PPO. UV-C/L-cys decreased PPO activity and had the highest aggregation index and turbidity of PPO. UV-C/L-cys further reduced the denaturation temperature point and increased the denaturation enthalpy of PPO. UV-C/L-cys turned the α-helix to random coil of PPO and destroyed the tertiary structure. This combined treatment aggregated the microstructure of PPO, which led to covering the active center of the enzyme, leading to its inactivation. Molecular docking simulation confirmed that L-cys bound to PPO through hydrogen bonding and ionic contact. This study established a foundation for the application of UV-C radiation and L-cys treatment to control food browning.